Mitologi dan Peranannya dalam Pemaknaan Artefak Purbakala: Studi Kasus Kapak Perunggu di Pura Puseh Timbul, Desa Pupuan, Kecamatan Tegalalang, Gianyar - Puja, Gusti Ngurah Ary Kesuma; Jayadi, I Kadek Surya (Humanis; Vol 27 No 3 (2023), 2023)
This study discuss about the bronze axe which is found in Banjar Timbul, Pupuan Village, Tegalalang District, Gianyar Regency. The artifacts originating from the perundagian period were chosen as the object of study in this research because there is an interesting relationship between the pre-historic heritage site and the meaning that the people of Banjar Timbul believe in the current era. The relationship is analyzed using a theory  of cultural assimilation which reads that a culture experiences a blend that eliminates the characteristics of the original culture that forms a new cultural pattern. The results of this study show that 1). The Bronze Axe in Banjar Timbul has shifted in function as well as its meaning by the community; 2). The mythology becomes a strong influential aspect in the shift of the bronze axe function in Banjar Timbul; 3). That behind the mythology of the Bronze Axe there are a numorous of hidden values, including: a symbol of protection, the majesty of ancestors, and a symbol of unity.